PENGARUH DIGITAL MARKETING DAN LITERASI KEUANGAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE DAN PERILAKU KONSUMTIF PADA GENERASI Z KOTA TANJUNGPINANG - ,Hj. Aida Nursanti, Muhammad Manbaul Ilmi ,Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Online shopping is a common activity carried out by various groups, especially the young population which is currently dominated by Generation Z. There are several factors influencing consumers when they want to shop online, including digital marketing  and  financial  literacy possessed  by consumers.  This study aims to determine to what extend these factors can influence online purchase decisions and consumptive behavior of Generation Z in Tanjungpinang city. Primary data collected with questionnaire as a research instrument. This study involved 108 people classified as Generation Z in Tanjungpinang City as respondents, using the Non-Probability sampling Technique. The data analysis technique used in this study is path analysis and assisted by the SPSS application version 25. The results of this study indicate that digital marketing has a positive and significant effect on online purchasing decisions and consumptive behavior. Financial Literacy has a negative and  significant effect on online purchase decisions and  consumptive behavior. Digital Marketing has a positive and significant effect on consumptive behavior through online purchase decisions. However, financial literacy has a negative and significant effect on consumptive behavior through online purchase decisions. Keywords: Digital Marketing, Financial Literacy, Online Purchase Decisions, Consumptive Behavior, Generation Z